Therapy with activated prothrombin complex concentrate is effective in reducing dabigatran-associated blood loss in a porcine polytrauma model - Honickel, Markus; Maron, Benjamin; Ryn, Joanne van; Braunschweig, Till; Cate, Hugo ten; Spronk, Henri M. H.; Rossaint, Rolf; Grottke, Oliver (Thrombosis and Haemostasis, 2016)
Clinical use of non-vitamin K antagonist oral anticoagulants is increasingly well established. However, specific agents for reversal of these drugs are not currently available. It was to objective of this study to investigate the impact of activated prothrombin complex concentrate (aPCC) on the anticoagulant effects of dabigatran in a randomised, controlled, porcine trauma model. Twenty-one pigs received oral and intravenous dabigatran, resulting in supratherapeutic plasma concentrations. Twelve minutes after injury (standardised bilateral femur fractures and blunt liver injury), animals (n=7/group) received 25 or 50 U/kg aPCC (aPCC25 and aPCC50) or placebo (control) and were followed for 5 hours. The primary endpoint was total volume of blood loss (BL). Haemodynamic and coagulation variables (prothrombin time [PT], activated partial thromboplastin time, diluted thrombin time, thrombin–antithrombin complexes, thromboelastometry, thrombin generation and D-dimers) were measured. Twelve minutes post-injury, BL was similar between groups. Compared with control (total BL: 3807 ± 570 ml) and aPCC25 (3690 ± 454 ml; p=0.77 vs control), a significant reduction in total BL (1639 ± 276 ml; p< 0.0001) and improved survival (p< 0.05) was observed with aPCC50. Dabigatran’s anticoagulant effects were effectively treated in the aPCC50 group, as measured by several parameters including EXTEM clotting time (CT) and PT. In contrast, with aPCC25, laboratory values were initially corrected but subsequently deteriorated due to ongoing blood loss. Thromboembolic or bleeding effects were not detected. In conclusion, blood loss following trauma in dabigatran-anticoagulated pigs was successfully reduced by 50 U/kg aPCC. Optimal methodology for measuring amelioration of dabigatran anticoagulation by aPCC is yet to be determined.
Keywords: Anticoagulants; aPCC; dabigatran; FEIBA; polytrauma; reversal; idarucizumab